Impact of Internet Big Data on Real Estate Marketing Strategy - Jie Wan (International Journal of Management and Education in Human Development, 2022)
In the gradual upgrading of the regulation policy of the real estate market, although the overall tone of the policy of "housing without speculation" has not changed, it poses a challenge to the operation of real estate companies. It is urgent for real estate companies to carry out transformation and development and improve their marketing strategy. This paper first expounds the current situation of real estate sales under the background of "Internet big data + real estate", then puts forward the problems faced in marketing, and finally gives a reasonable marketing strategy.